Theoretical foundations of emerging economy business research - Meyer, Klaus E; Peng, Mike W (Journal of International Business Studies, 2016)
In “Probing Theoretically into Central and Eastern Europe: Transactions, Resources, and Institutions,” we outlined the contributions of research in Central and Eastern Europe (CEE) to theoretical debates in business research. In this retrospective, we reflect upon the evolution of the field over the past decade. With the fading impact of CEE’s distinct shared history, we suggest that CEE best be analyzed as emerging economies, rather than as a distinct geographic entity. Emerging economy business research is converging on common themes and shared theoretical ideas, while identifying critical variations that constrain generalizations among and beyond emerging economies. This research thus highlights the need to develop a better understanding of the boundary conditions of scholarly theories of business knowledge. Over the past decade, the institution-based view has emerged from distinct intellectual traditions in institutional economics, organizational theory, and the analysis of business–government bargaining. Research in these converging lines of theorizing places contextual variations at the center of explanations of business phenomena around the world. We suggest that the institution-based view is evolving toward a paradigm, and offer suggestions on how to advance this research agenda further, in particular by exploring how firms engage with different sets of potentially conflicting institutions at multiple levels and locations.